Fundamentals of Conceptualization of Family Relationships in the Republic of Uzbekistan - E.I.Акramova (Zien Journals, 2022)
this article examines aspects of family relationships, the sociological approach of intergenerational relationships, historical changes in relations between institutions and the role of family transformations in transforming the foundations of social life
Keywords: family; family intergenerational relationships; historical changes; transformation